Modelo de encriptación simétrica basada en atractores caóticos - Amaya Barrera, Edilma Isabel; Suárez Parra, César Augusto; Huérfano Ortiz, Rafael Esteban; Moreno Posada, José David; Parra Fuentes, Fabio Andrés (Ingeniería, 2016)
Context: the increase in the processing capacity of machines and developments in combinatorial search algorithms reduces the time required to decipher the information fraudulently. Bear in mind this, there is a need to generate new ways of encoding information for secure transmission. Method: in this paper a symmetrical and extensible model for digital communications encryption is presented, taking advantage of the chaos generated by nonlinear dynamic systems. Results: the developed model proved to encrypt messages in time synchronization, encryption and decryption less than 1 ms with an entropy higher than 6 using the Rössler attractor for its implementation. Conclusions: the algorithm is presented as an alternative to traditional algorithms demonstrating greater efficiency in the management of computing resources and raises the groundwork for continuing their study on the interested academic community due to the variety of dynamical systems nonlinear.